Correlation between depression level and headache severity: A study among medical students during the COVID-19 pandemic - Bintari, Dika C.; Sudibyo, Devi A.; Karimah, Azimatul (Narra Sains Indonesia, 2021)
Headache is the most prevailing disorder and the third leading cause of disability worldwide. The prevalence of primary headaches has been reported to increase by 2-4 times in patients with psychiatric comorbidities, including depression. This study sought to assess the correlation between depression level and headache severity among medical students. To the best of our knowledge, this is the first study to evaluate the correlation between depression level and headache severity in Indonesia. A cross-sectional study was conducted among students of Airlangga University in 2021. To evaluate the level of depression and the severity of headache, Depression Anxiety Stress Scales (DASS-42) and Headache Impact Test 6 (HIT-6) were used, respectively. A set of validated questionnaires were used to assess students’ demographic characteristics. A total of 82 medical students were included in this study and most of them were female (86.6%). The third-semester students represented the highest proportion (45.2%) of subjects. The mean age and body mass index (BMI) were 19.88 ± 1.03 and 22.55±4.44, respectively. The average DASS-42 score was 10.98±11.47 which indicated a mild depression level. The average HIT-6 score was 45.74±6.130 which revealed a mild impact. The data of Spearman correlation suggested that headache severity was significantly correlated with depression level (r=0.396, p<0.001). This study provides insights on the importance of stress management and depression prevention to decrease the risk of headache, and vice versa.